The Effect Of Using Memrise On Maharah Qira'ah Among The Seventh Grade Students At Mtsn 1 Malang City - Aulia Subita; Mohammad Ahsanuddin; Romyi Morhi (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
This present research was aimed at describing (1) the learning of reading Arabic using Memrise and (2) the effect of the use of Memrise on the reading skills among the seventh-grade students at MTsN (State Islamic Junior High School) 1 Malang City. Reading in this present research is learning to read vocabulary and sentences. This research adopted a quantitative approach where the subjects were the seventh grades E and H students at MTsN 1 Malang City in learning Arabic using Memrise. The students were asked to learn online independently. The data were obtained from the test results. The data source was respondents from the students of seventh Grades E and H. The research instruments were pretests and posttestsposttests. The data analysis technique used was the t-test. The results showed the following: (1) the learning of reading Arabic using Memrise was carried out through the following steps: learning the material, pronouncing words, interpreting words according to pictures, and doing quizzes. (2) Based on the results of the t-test, it can be concluded that using Memrise in learning Arabic can positively affect students' reading skills. Keywords: Reading skills, Memrise. الملخص يهدف هذا البحث الحالي إلى وصف (1) تعلم قراءة اللغة العربية باستخدام ميمريس و (2) تأثير استخدام ميمريس على مهارات القراءة بين طلاب الصف السابع في المدرسة الثانوية الحكومية الأولى مالانج. تعلم القراءة المشار إليه في هذا البحث هو قراءة المفردات والجمل. اعتمد هذا البحث نهجًا كميًا حيث كان الموضوع طلاب الصف السابع E و H في المدرسة الثانوية الحكومية الأولى مالانج في تعلم اللغة العربية باستخدام ميمريس. طُلب من الطلاب التعلم عبر الإنترنت بشكل مستقل. تم الحصول على البيانات من نتائج الاختبار. كان مصدر البيانات عبارة عن مستجيبين من طلاب الصف السابع E و H. كانت أدوات البحث عبارة عن اختبارات تمهيدية وبعدية. كانت تقنية تحليل البيانات المستخدمة هي اختبار T. أظهرت النتائج ما يلي: (1) تم تعلم قراءة اللغة العربية باستخدام ميمريس من خلال الخطوات التالية ، وهي تعلم المادة ، ونطق الكلمات ، وتفسير الكلمات وفقًا للصور ، وإجراء الاختبارات القصيرة. (2) بناءً على نتائج اختبار t ، يمكن استنتاج أن استخدام ميمريس في تعلم اللغة العربية يمكن أن يكون له آثار إيجابية على مهارات القراءة لدى الطلاب. الكلمات الرئيسية: مهارة القراءة, ميمريس